2013
DOI: 10.3390/ijms15010377
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure of Siberian apricot (Prunus sibirica L.) in China

Abstract: The genetic diversity and population genetic structure of 252 accessions from 21 Prunus sibirica L. populations were investigated using 10 ISSR, SSR, and SRAP markers. The results suggest that the entire population has a relatively high level of genetic diversity, with populations HR and MY showing very high diversity. A low level of inter-population genetic differentiation and a high level of intra-population genetic differentiation was found, which is supported by a moderate level of gene flow, and largely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 58 publications
(70 reference statements)
7
23
0
Order By: Relevance
“…In our study, a relatively high level of genetic diversity was detected at microsatellite loci in Siberian apricot; the mean Ho and He values were 0.639 and 0.774, respectively. Similar values were reported for populations of Siberian apricot in the Yan Mountains (Ho = 0.668, He = 0.788) [15]. Fewer polymorphisms have been reported for apricot ( Prunus armenica L.; Ho = 0.615, He = 0.621) [41].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In our study, a relatively high level of genetic diversity was detected at microsatellite loci in Siberian apricot; the mean Ho and He values were 0.639 and 0.774, respectively. Similar values were reported for populations of Siberian apricot in the Yan Mountains (Ho = 0.668, He = 0.788) [15]. Fewer polymorphisms have been reported for apricot ( Prunus armenica L.; Ho = 0.615, He = 0.621) [41].…”
Section: Discussionsupporting
confidence: 78%
“…Outcrossing woody plants tend to be more genetically diverse and have less genetic differentiation among populations [32]. The percentage of genetic variation within populations of Siberian apricot in the Yan Mountains was shown to be up to 96% [15]. The negative percentage of variation detected among wild and semi-wild groups suggests that there is no significant difference between them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise in a similar type of study Kumar et al (2014) reported RAPD makers more informative than ISSRs in Justicia adhatoda. Furthermore, significant correlation between similarity matrices generated by ISSR and SSR (r = 0.500, t = 10.774, p = 1.00) markers are in confirmation with earlier reports of association between ISSR and SSR markers by Budak et al (2004) and Li et al (2014) in buffalo grass and Siberian apricot, respectively. The ISSR and SSR markers used in present study would be very useful for germplasm characterization of roselle.…”
Section: Marker Polymorphism and Genetic Diversity Parameterssupporting
confidence: 89%
“…Siberian apricots in China were divided into two subpopulations (Li et al, 2014) and into four subpopulations in another study (Wang et al, 2014), and molecular findings have shown that no significant difference is detected between the wild and semiwild groups, indicating that recent cultivation practices have had little impact on the genetic diversity of Siberian apricots (Wang et al, 2014). The common apricots of Mediterranean countries were studied by Bourguiba et al (2012), and 207 accessions were subdivided into three main gene pools when K = 3: Irano-Caucasian, North Mediterranean Basin and South Mediterranean Basin.…”
Section: Discussionmentioning
confidence: 99%